2015
DOI: 10.1038/nm.3885
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of amyloid-β plaque formation by α-synuclein

Abstract: Amyloid-β (Aβ) plaques and α-synuclein (α-syn)-rich Lewy bodies are the major neuropathological hallmarks of Alzheimer's disease (AD) and Parkinson's disease, respectively. An overlap of pathologies is found in most individuals with dementia with Lewy bodies (DLB) and in more than 50% of AD cases. Their brains display substantial α-syn accumulation not only in Lewy bodies, but also in dystrophic neurites decorating Aβ plaques. Several studies report binding and coaggregation of Aβ and α-syn, yet the precise ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 42 publications
4
92
1
Order By: Relevance
“…First, recent studies reported that the overexpression of the A30P mutant of human αSyn in APP/PS1 Tg mice, another model of AD, led to a lowering of Aβ deposition and to synaptic abnormalities suggestive of synapse loss (53). The alterations in synaptic proteins observed in 3-mo-old bigenic J20×TgI2.2 mice appear reminiscent of those reported by Bachhuber et al despite qualitative differences.…”
Section: Synapsin-i/ii Lowering and Cognitive Deficits In Ad And Animalmentioning
confidence: 61%
“…First, recent studies reported that the overexpression of the A30P mutant of human αSyn in APP/PS1 Tg mice, another model of AD, led to a lowering of Aβ deposition and to synaptic abnormalities suggestive of synapse loss (53). The alterations in synaptic proteins observed in 3-mo-old bigenic J20×TgI2.2 mice appear reminiscent of those reported by Bachhuber et al despite qualitative differences.…”
Section: Synapsin-i/ii Lowering and Cognitive Deficits In Ad And Animalmentioning
confidence: 61%
“…In vitro data show an induction of abeta aggregation by alpha-synuclein 7 . In contrast, a more recent study detected decreased abeta deposits due to injection of alpha-synuclein containing homogenates or preformed alpha-synuclein fibrils in hippocampus of an AD mouse model 8 . However, cross-seeding activity of alpha-synuclein has been hypothesized to be the molecular consequence of alphasynuclein inclusions in 60% of AD patients 4,9 .…”
mentioning
confidence: 71%
“…The reason for this is unclear, but one possibility is that the injections of α-synuclein-containing preparations inhibit plaque formation in the brains of Aβ precursor protein transgenic mice, as recently shown in basic research [30]. Aβ fibril formation was also reduced in the presence of α-synuclein in an in vitro aggregation assay.…”
Section: Discussionmentioning
confidence: 94%
“…However, FBB likely does not bind to the nonfibrillar oligomeric forms of Aβ, which have been suggested as being more toxic than the Aβ plaques in the pathogenesis of AD-related neuronal dysfunction and memory deficits [40]. The inhibition of Aβ fibril formation and deposition can increase toxic Aβ oligomers, thereby leading to neurodegeneration despite reduced Aβ plaque load [30]. Thus, it is premature to conclude that Aβ toxicity does not contribute to cognitive impairment in PD with negative amyloid PET results.…”
Section: Discussionmentioning
confidence: 99%